Persepsi Masyarakat terhadap Penggunaan Transportasi Online (Go-Jek) di Kota Pematangsiantar - Rizki Alfadillah Nasution; Ilham Syahputra Saragih (Publikasi Indonesia, 2022)
Ojek Online is currently mushrooming as a means of transportation that is in demand by the public. This is based on the effectiveness and efficiency offered and is the main attraction for its users. This study aims to determine public perceptions of the use of Gojek online transportation in Pematangsiantar City. The population defined in this study are consumers of online transportation users taken from the background of age, gender and occupation. Sampling technique using a questionnaire. This type of research is a quantitative descriptive research, where the researcher tries to describe the subject or subject being studied in accordance with the data obtained. The data analysis technique in this research uses validity test, reliability test and t one sample test. The results of this study indicate that from the results of the t-test one sample test, the t-value (count) is 49,546. The value of df (degree of freedom) or the degree of freedom is 49. The value of sig.(2-tailed) is 0.000. Thus the alternative hypothesis (Ha) which reads that the public has a good perception of the existence of Gojek online transportation in Pematangsiantar City is accepted.